FEM-Based Seismic Response Analysis of Landslide Occurrence Areas in the 2024 Noto Peninsula Earthquake - Li, Yuanying; Iino, Haruka; Saito, Sota; Wakai, Akihiko (Journal of disaster research, 2025)
At 16:10 (JST) on January 1, 2024, a magnitude M j 7.6 earthquake struck the northern Noto Peninsula, Japan. The earthquake caused intense ground shaking, with the peak ground acceleration (PGA) reaching 2,828 gal, which is one of the highest values ever recorded. Over 2,300 landslides were triggered, causing severe damage to infrastructure. The Noto Peninsula has long been vulnerable to significant seismic activity and has experienced a sustained seismic swarm from November 2020 to May 2023, during which at least 20,000 earthquakes with magnitudes of M j ≥1.0 were recorded. In mountainous areas, earthquakes are often accompanied by coseismic landslides. Owing to the frequent seismic swarm activity in the Noto Peninsula, long-term vigilance is essential to mitigate the hazards of earthquake-induced landslides and related secondary disasters. This study focuses on the Okubo District of Wajima City, Ishikawa Prefecture, which experienced a high concentration of landslides during the earthquake, including the largest observed landslide. A 3D dynamic elastoplastic finite element method was applied to simulate seismic ground responses and reassess the landslides triggered by the earthquake. The simulation emphasizes the spatial distribution of shear stress and PGA during seismic loading. Comparing the simulation results with the observed landslide inventory reveals that zones of elevated shear stress and PGA generally correspond to documented landslide locations. These findings suggest that the proposed numerical modeling approach can effectively identify potentially high-hazard slopes over a wide area, thereby supporting the development of a landslide-susceptibility map for the earthquake-prone Noto Peninsula.